How supportive supervision influences immunization session site practices: a quasi-experimental study in Odisha, India - Panda, Bhuputra (Glob Health Action, 2015)
BACKGROUND: Routine immunization (RI) is a key child survival intervention. Ensuring acceptable standards of RI service delivery is critical for optimal outcomes. Accumulated evidences suggest that ‘supportive supervision’ improves the quality of health care services in general. During 2009–2010, the Government of Odisha and UNICEF jointly piloted this strategy in four districts to improve RI program outcomes. The present study aims to assess the effect of this strategy on improvement of skills and practices at immunization session sites. DESIGN: A quasi-experimental ‘post-test only’ study design was adopted to compare the opinion and practices of frontline health workers and their supervisors in four intervention districts (IDs) with two control districts (CDs). Altogether, we interviewed 111 supervisor–supervisee (health worker) pairs using semi-structured interview schedules and case vignettes. We also directly observed health workers’ practices during immunization sessions at 111 sites. Data were analyzed with SPSS version 16.0. RESULTS: The mean knowledge score of supervisors in CDs was significantly higher than in intervention groups. Variegated responses were obtained on case vignettes. The control group performed better in solving certain hypothetically asked problems, whereas the intervention group scored better in others. Health workers in IDs gave a lower rating to their respective supervisors’ knowledge, skill, and frequency of supervision. Logistics and vaccine availability were better in CDs. CONCLUSION: Notwithstanding other limitations, supportive supervision may not have independent effects on improving the quality of immunization services. Addressing systemic issues, such as the availability of essential logistics, supply chain management, timely indenting, and financial resources, could complement the supportive supervision strategy in improving immunization service delivery.